Management Of Ashmari (~Renal Calculi) Through Ayurveda (Journal of Pharmaceutical Negative Results, 2023)
Renal stone or Kidney stone is correlated to Ashmari in Ayurveda, and it has a comprehensive approach with effective oral medications for treatment. A 29-year-old male patient had come to the OPD of CARI Guwahati for 10 days complaining of vomiting, lower back pain and dysuria. Patient had also brought the report of their ultrasonography done on 31.07.2021. No other abnormality was detected during the general and systemic examination. The report mentioned about three renal calculi measuring 4.2 mm and 4.8 mm in Right Kidney and 4.2 mm in Left Kidney. The patient was prescribed Gokshuradi Guggulu, Chandraprabha Vati, Pashanabhedadi Kwatha and Shwet Parpati on OPD basis. There was improvement in clinical features like pain and dysuria after taking ayurvedic medicine. Ultrasonography scan did not reveal any renal calculus dated on 22.10.2021. So, it can be concluded that Gokshuradi Guggulu, Chandraprabha Vati, Pashanbhedi Kwatha and Shwet Parapati have given relief in the symptoms. This case shows that traditional Ayurvedic medicines are effective in the management of Ashmari (~renal stone).